ANALYSIS ON THINKING SKILL: COGNITIVE LOAD MANAGEMENT IN CONNECTED INTEGRATED LEARNING (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2020)
Connecting related concepts can enable learners to obtain holistic knowledge but designing integrated learning must consider high element interactivity between concepts, so that learning would not result in excessive cognitive load, which will instead hinder learning. The promising benefit of learning plant anatomy and physiology in connected integrated learning was analyzed by assessing preservice biology teachers’ identification and information analysis skills. The influence of learning approach on their cognitive load was also analyzed. Results suggested the advantage of learning in an integrated way, in which cognitive load can be managed by considering the correlation between cognitive load elements.
Keywords: Thinking Skills; Integrated Learning; Plant Structure; Plant Physiology; Cognitive Load; Preservice Biology Teachers